Value and Vulnerability Assessment of a Historic Tomb for Conservation - Aykut Erkal; Hakki O. Ozhan (The Scientific World Journal)
Monumental tombs reflect various social, cultural, architectural, religious, economic, and engineering features of a community. However, environmental weathering, natural disasters, poor maintenance, vandalism, and misuse unfortunately pose serious threats to these cultural assets. Historic monuments are often exposed to the highest risk due to their vulnerability. The Ottoman-style Nişancı Hamza Paşa tomb located in Karacaahmet Cemetery, Istanbul, the largest and oldest public cemetery in Turkey, is a case in point. The tomb consisting of six granite columns and a brick dome supported by six arches was constructed in 1605. Cracks, material loss, and decay as a result of adverse environmental effects and past earthquakes are evident. Therefore, this paper analyses the overall value of the tomb with respect to its historical, communal, evidential, and aesthetic aspects. Using the finite element approach and data on the tomb’s material properties, a structural analysis under the self-weight and a time history analysis based on the earthquake ground motion data recorded in Duzce, Turkey, in November 1999 were conducted to encourage the conservation of this tomb and similar cultural heritage assets all over the world. The damage observed in the structure is congruent with the analysis results.